INFLUENCE OF TEACHER FEATURES ON INSTRUCTIONAL QUALITY IN PUBLIC SECONDARY SCHOOLS IN THE SOUTH-WEST, NIGERIA - Awolola , Oluwatoyin; Alabi, Christianah (African Journal of Education and Practice, 2022)
Purpose: In contemporary time, delivery of undesirable instructional quality (IQ) in Nigeria's education system, particularly in public secondary education has gradually become a serious concern to education stakeholders. The challenge seemly to be associated with teacher factors (such as qualification, experienced and professionalism) among other factors. Thus, this study investigated influence of teacher features on instructional quality in public secondary schools in the South-west, Nigeria. Methodology; This study adopted descriptive survey research design. Multi-stage sampling procedure was employed. Random sampling technique was used to select 1,440 respondents (1,200 teachers and 240 principals) which were in 240 public secondary schools in Southwest, Nigeria. One self-design and adopted rating scale were scrutinized and validated by experts from the field of Evaluation and Management, after which modifications was made. Teacher Factor Questionnaire (r = 0.87) and Instructional Quality Rating Scale (r = 0.85) were administered. Pearson Product Moment Correlation Coefficient Analysis and Multiple Regression Analysis were employed to answer three research questions and test one hypothesis at 0.05 level of significance respectively. Findings: The results revealed that there is a significant positive relationship between teacher qualification and IQ (r = 0.28; p< 0.05); teacher experience; (r = 0.27; p< 0.05) and teacher professionalism (r = 0.30; p<0.05). The composite relationship between all the independent variables and dependent variable further revealed that R = 0.40. Professionalism had the highest significant influence on IQ (Î²= 0.29; t= 3.24; p <0.05); followed by teacher experience (Î² = 0.22; t = 5.54; p<0.05) and qualifications, (Î² = - 0.03; t = -0.37; p>0.05). This led to the fact that the independent variables accounted for 15.3% of the total variance in the IQ in public secondary schools in Southwest (Adjusted R2 = 0.153). This composite influence is shown to be statistically significant (F (7, 606) = 16.83; p < 0.05. Unique Contribution to theory, practice and policy: The study uncovered and pointed the influence of teachers' professionalism, experience and education qualification as a major dependable and benchmarks for achieving IQ in the school setting. The adopted Systems theory clarifies intra-relationship of each variable with IQ and inter-relationship among the variables in the study. Likewise, it confirmed IQ as a fundamental factor to the success of the school operation. Moreover, it established the transformation process (in teaching-learning process), which in turn enhance achieving educational objectives and school's future productivity.